Technical Efficiency and Growth of Banks: A Bibliometric Analysis - Mangal Chhering (European Economic Letters (EEL), 2025)
This study delves into the complex relationship between technical efficiency and growth of the banks using a bibliometric approach. While it is commonly believed that efficient banks should grow, the literature on this relationship remains sparse and ambiguous. Our research aims to identify and analyze key publications, authors, academic affiliations, source titles, countries, languages, document types, subject areas, and citation matrices addressing above issue. By examining these factors, we seek to offer valuable insights for guiding future research in this field. This study employs a bibliometric analysis to investigate the current trends and patterns in the research on technical efficiency and growth of the banks. By analyzing 217 documents sourced from the Scopus database, the study identifies key research areas, influential authors, and significant publications. The most cited papers were written in 2002 (468 total citations), 'Economics, Econometrics, and Finance' being the dominant subject area (32.68% publications). Articles being the most published (87.55%), English is the key language (96.8%), the United States is the top country (31 publications), and 'Journal of Banking and Finance' is an important journal (11 publications). Isik, I. is the most influential author (705 total citations). This study elucidates publications pertaining to the technical efficiency and growth of banks, encompassing key contributors, authors, countries, journals, publishers, and significant keywords. Researchers can leverage this paper for their further investigations, particularly in establishing the relationship between technical efficiency and the growth of banks. The study is constrained by its limitation that only Scopus database has been employed to the analysis. Our paper is first of its kind in exploration into the relationship between technical efficiency and the growth of banks using bibliometrics method.